2019
DOI: 10.3390/su11020378
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Promotion of Two Salt-Tolerant Plant Groups with PGPR Inoculation: A Meta-Analysis

Abstract: Understanding the primary mechanisms for plant promotion under salt stress with plant growth promoting rhizobacteria (PGPR) inoculation of different salt-tolerant plant groups would be conducive to using PGPR efficiently. We conducted a meta-analysis to evaluate plant growth promotion and uncover its underlying mechanisms in salt-sensitive plants (SSP) and salt-tolerant plants (STP) with PGPR inoculation under salt stress. PGPR inoculation decreased proline, sodium ion (Na+) and malondialdehyde but increased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
35
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 63 publications
11
35
1
3
Order By: Relevance
“…In our investigation, leaf MDA content was significantly lower in plants pre-inoculated with B. amyloliquefaciens 54 ( Figure 3C). The result is consistent with previous studies, in which PGPR was shown to decrease the MDA content of plants under abiotic stress conditions [65,66]. Moreover, hyper-robust biofilms increased leaf MDA content, while defective biofilms decreased leaf MDA content compared to that in plants treated with the wild-type strain ( Figure 3C), suggesting that B. amyloliquefaciens 54 biofilm formation protects cell membranes from ROS and decreases lipid peroxidation, thereby enhancing drought tolerance.…”
Section: Discussionsupporting
confidence: 92%
“…In our investigation, leaf MDA content was significantly lower in plants pre-inoculated with B. amyloliquefaciens 54 ( Figure 3C). The result is consistent with previous studies, in which PGPR was shown to decrease the MDA content of plants under abiotic stress conditions [65,66]. Moreover, hyper-robust biofilms increased leaf MDA content, while defective biofilms decreased leaf MDA content compared to that in plants treated with the wild-type strain ( Figure 3C), suggesting that B. amyloliquefaciens 54 biofilm formation protects cell membranes from ROS and decreases lipid peroxidation, thereby enhancing drought tolerance.…”
Section: Discussionsupporting
confidence: 92%
“…These results are also consistent with other AMF-inoculated plant species, such as citrus [62], Leymus chinensis [76], and black locust [77]. The enhancement of photosynthesis may be caused by 1) growth promotion in the leaf and stem, which improves light interception and utility, and further benefits the photosynthetic capacity [28], 2) the optimization of the root structure, which is beneficial to the absorption of water and nutrients (such as nitrogen and magnesium), further promoting photosynthesis [24], and 3) combined enhancements in both gas exchange capacity and CO 2 diffusion speed are instrumental in photosynthesis [78].…”
Section: Discussionsupporting
confidence: 81%
“…The potential of ST-PGPR can be harnessed for the improvement of crop yield of saline soils. According to Pan et al (2019) physiological roles played by ST-PGPR could improve plant performance under saline conditions. It has been realized that elucidation of mechanisms of osmo-adaptation in ST-PGPR may contribute to the long-term goal of improvement of productivity in crops grown in saline agro-ecosystems (Paul, 2013).…”
Section: Future Prospectsmentioning
confidence: 99%